A retrospective study of oral maxillary squamous cell carcinomas treated from 2008-2018. Issue 1 (January 2022) - Gamie, Yehya; Brown, James; Lowe, Derek; Triantafyllou, Asterios; Rogers, Simon
Abstract : Introduction: Controversy exists regarding the management of the clinically node negative neck (cN0) in maxillary or gingival squamous cell carcinoma (MGSCC). This study reviews cN0 MGSCC patients over a 10-year period to record the method of neck management and outcome. Methods: Theatre and pathology records were searched for patients diagnosed and treated for site specific cN0 MGSCC from 2008-2018. The Fisher's exact test was used for comparative analysis and survival statistics calculated using the Kaplan–Meier method and log-rank test. Results: 15/36 of patients had an END and 21/36 underwent observation following primary surgery. Included in these 21 patients, 5 underwent vessel access for flap anastomosis with node sampling. 13/36 of patients received PORT. The total recurrence rate was 15/36; 5/15 local, 8/15 regional and 2/15 with locoregional. Regional recurrence was similar in observed patients 5/21 compared to those who had an END 3/15. 8/15 of patients with recurrence underwent salvage surgery. Salvage rates were 3/7 in patients who received PORT and 5/8 without, with success in 2/3 and 4/5 respectively. Conclusions: END 5- year disease specific survival (DSS) (67%) was similar to observed patients (65%) although those with vessel access had a 80% DSS (p=0.87). pT4a END patients had a higher 5- year DSS versus observation only patients (56% vs 44%) (p=0.53). Bone invasion was significant to RL (p= 0.05). There was no advantage to having an END for the N0 neck in MGSCC and control was also achieved with a 'watch and wait' policy followed by salvage if required.